A persistent increase in gut permeability correlates with emotional dysregulation following maternal separation in male and female mice - Castro-Zavala, Adriana; Nieto-Nieves, Ana; Melgar-Locatelli, Sonia; Medina-Rodríguez, Lidia; Mañas-Padilla, María del Carmen; Castilla-Ortega, María Estela (Elsevier, 2025)
Early life stress (ELS) significantly influences vulnerability to psychiatric disorders in adulthood. A widely used preclinical model for studying ELS is maternal separation with early weaning (MSEW), which mimics early-life neglect. This study evaluated the impact of ELS induced by MSEW on emotional behaviour, intestinal permeability, and neuroinflammatory markers in male and female mice. Our results show that MSEW increases anxietylike behaviours in adulthood, particularly in females, and exacerbates depression-like behaviours and anhedonia in both sexes. Notably, increased intestinal permeability correlated with higher anxiety and depression-like responses, suggesting a crucial role of gut health in emotional regulation. These alterations were long-lasting, indicating persistent effects on gut function following ELS. Additionally, MSEW animals exhibited higher hippocampal BDNF expression, particularly males. However, there were no significant differences in the long-term survival of adult-born hippocampal cells, as indicated by BrdU+ labelling. Both sexes showed increased NF-κB protein levels; however, only MSEW males exhibited TNF-α changes, suggesting a sex-specific regulatory mechanism in response to chronic stress. This study highlights intestinal permeability as a key mechanism linking ELS to emotional and behavioural dysregulation. By demonstrating a long-lasting increase in intestinal permeability and its correlation with mood disorders, our findings extend the gut-brain axis hypothesis to ELS. The inclusion of both sexes provides a more comprehensive understanding of sex-specific effects of early stress, often overlooked in previous research.
This study was funded by Grant PID2020–114374RB-I00 from MCIN/AEI/10.13039/501100011033 (to E.C-O.), Universidad de M´alaga (B.1. Ayudas para proyectos dirigidos por j´ovenes investigadores B1–2022_05 to A.C.-Z,), and Universidad de M´alaga (C.2. II Plan Propio de Investigaci´on, Transferencia y Divulgaci´on Científica). Funding for open access charge: Universidad de M´alaga / CBUA. A.C.Z. holds a postdoctoral research contract from the Secretaría General de Uni versidades, Investigaci´on y Tecnología–Junta de Andalucía ( DOC21_00365) and a Sara Borrell contract from the Instituto de Salud Carlos III (CD24/00041). A.N.-N. holds a predoctoral grant from the Spanish Ministry of Science, Innovation and Universities (FPU22/ 02044).
Keywords: Ansiedad de separación en niños; Intestinos -- Microbiología; Emociones; Afecto (Psicología); Early life stress; Maternal separation; Gut-brain axis; Neuroinflammation; Intestinal permeability; Anxiety; Depression